LINK between Degeneration and Regeneration of Human Intervertebral Discs. (May 2014) - Mwale, Fackson; Gawri, Rahul; Ouellet, Jean; Önnerfjord, Patrik; Alkhatib, Bashar; Steffen, Thomas; Heinegård, Dick; Roughley, Peter; Antoniou, John; Haglund, Lisbet
Back pain affects a large portion of the population across all ages and intervertebral disc (IVD) degeneration is its most implicated common cause. Presently, there are no established treatments to prevent, stop, or even retard disc degeneration, and surgery is often the offered option. Previous studies have shown that Link N can act as a growth factor and stimulate the synthesis of proteoglycans and collagens in bovine IVD in vitro and in intact human IVDs ex vivo, as well as increase disc height in a rabbit model of disc degeneration. However, the sequences in Link N involved in modulating cellular activity are not well understood. To determine if disc cells can proteolytically process Link N, human disc cells in monolayer were exposed to native Link N over a 48-hour period and mass spectrometric analysis revealed that a peptide spanning residues 1 to 8 was generated in the presence of AF cells but not NP cells. Link N 1-8 significantly induced proteoglycan production in the presence of IL-1β in both NP and AF cells, confirming that the biological effect is maintained in the first eight amino acids of the peptide and indicating that the effect is sustained in an inflammatory environment. Thus Link N 1-8 could be a promising candidate for biologically induced disc repair, and the identification of such a stable specific peptide may facilitate the design of compounds to promote disc repair and provide alternatives to surgical intervention for early stage disc degeneration. Acknowledgments The authors thank Ms. Areej Khabut for her assistance with mass spectrometry. This work would not have been possible without funding from the Faculty of Medicine McGill University, AO Spine, North American Spine Society and Canadian Institutes of Health Research. We also thank Transplant Quebec for coordinating the retrieval of human lumbar spines through their organ donation program. Lastly, we thank The Crafoord Foundation and the Inga-Britt & Arne Lundberg Foundation for funding the mass spectrometers used in this study. Disclosure of Interest None declared